Thirdkey Business Plan - Skilton, Chris (2009)
This document is a five year business plan is for Thirdkey Ltd, a training and coaching business based in Nottingham. Thirdkey Ltd has developed from Thirdkey Social Enterprise Solutions a specialist consultancy founded by Chris Mahon in 2004 to serve the social sector. Now Chris Skilton is joining the business to take over day to day operations and oversee the expansion of Thirdkey into a larger training organisation.